Michal Ďurčo, Cesty a diaľnice na Slovensku v medzivojnovom období. Nástup automobilovej doby v znamení Československej Republiky [Roads and Highways in Slovakia during the Interwar Period. The Beginning of the Era of the Automobile under the Sign of the Czechoslovak Republic] (Bratislava: VEDA vydavateľstvo SAV - Historický ústav SAV, 2020), 230 pages - MÂRZA, Radu (Studia Universitatis Babeș-Bolyai Historia, 2025)
A few years ago, a book was published in Bratislava that, at least for Romanian historiography, deals with an unusual theme. While the field of railway history has produced a substantial body of scholarly literature (in Romania), the history of road transport is only beginning to emerge as a field of study. The book written by historian Michal Ďurčo, a researcher at the Institute of History of the Slovak Academy of Sciences in Bratislava, is a history of road transport in Slovakia during the Interwar period. The subject is by no means easy, and yet the author did not make it any easier for himself. He made a great documentation effort, which involved going through an impressive bibliography of hundreds of journal articles, volumes, monographs, etc., but he also visited 12 archives on the territory of Slovakia, where he consulted numerous fonds (government institutions, local administration). We have provided these details, which are normally written at the end of a review, from the very beginning in order to emphasize the effort made by the author. The result is a complex and comprehensive book. It has a logical structure, starting with general considerations and aspects of the history of the subject it focuses on, before moving on to the subject itself and its details.